Malaria in a cohort of Javanese migrants to Indonesian Papua. - Krisin; Basri, H; Fryauff, D; Barcus, M; Bangs, M; Ayomi, E; Marwoto, H; Elyazar, I; Richie, T; Baird, J (2003)
The epidemiology of infection by Plasmodium falciparum and P. vivax was investigated among Javanese migrants to an endemic region of Papua, Indonesia. A cohort of 243 migrants from Java was followed for malaria in a new settlement village in the endemic Armopa area of north-eastern Papua, beginning on the day each migrant arrived in the village. The subjects were monitored during home visits (three/week) and by the twice-monthly production of bloodsmears that were checked for malarial parasites. At the end of 33 months, 159 (65%) of the subjects remained under follow-up. The prevalence of parasitaemia in the village declined from 16% among those already living there when the study began in August 1996, to 5% when the study finished in June 1999. Over this period, 596 infections by P. falciparum and 723 by P. vivax occurred in the cohort, 22 and 27 of the subjects each experiencing at least six infections by P. falciparum and P. vivax, respectively. The incidence of malarial infection was higher during the first and second years post-migration (3.2 and 2.7 infections/person-year) than during the third (1.2 infections/person-year). Although the geometric mean parasite counts for P. falciparum increased over time (1209, 1478, and 1830 parasites/microl in the first, second and third years, respectively), the corresponding values for P. vivax (497, 535 and 490 parasites/microl) showed no such trend. Only one of the nine subjects who developed severe malaria (requiring intravenous quinine therapy) was a child, giving an odds ratio for a case of severe malaria being in an adult of 6.1 (P=0.08).